A Review on Vyanga vis a vis Melasma - Sharma, Sourabh; Samyal, Komal (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda is one of the oldest comprehensive health care system worldwide. Ayurvedic science being ancient and traditional still correlate with day to day medical conditions and their treatment. Melasma being a non communicable and non deteriorated condition is still a mental trauma in human life especially for the younger age group. Melasma is a common acquired condition of symmetrical hyper pigmentation typically occurring on the face with higher prevalence in females and darker skin types. It is is characterized by more or less dark brownish maculae with irregular contour , but clear limits on photo exposed areas especially on the face, forehead, temples and more rarely on the nose, eyelids, chin and upper lips. In Ayurveda, vyanga has been elaborated as one of the kshudra rogas (minor ailments). VYANGA, a type of kshudra Roga, characterized by niruja (painless), shayav varna mandala (bluish black patches) occurring specially on the face. The clinical features correlate with melasma which is acquired and symmetrical hypermelanosis . Vyanga is a disease which belongs to swalpa variety of kshudra Roga. Vayu aggravated by Krodh and ayasa, get associated with pitta and suddenly produces a thin grey coloured circular patch which reaches the face. As per medical science melasma, cutaneous pigmentation is the outcome of two important events, the synthesis of melanin by melanocyte and the transfer of melanosomes to surrounding Keratinocytes. Both modern and ayurvedic sciences have considered the use of topical as well as oral medications and their combinations for the treatment of vyanga. In Ayurveda,vyanga has been treated both by antah parimarjan and bahya parimarjan chikitsa. Several ayurvedic text such as Sushruta Samhita and Ashtanga Hridaya and Sangraha etc, have elaborated the pathophysiology and treatment of vyanga, the available references are scattered. So, there is a need of in-depth review and compilation of ayurvedic text and literatures which are effective for the management of vyanga.